DETERMINAN PREDIKSI KRISIS PERBANKAN BERBASIS BANKING SECTOR FRAGILITY INDEX - Dian Hamida; Nurmala Ahmar; Syahril Djaddang (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2017)
The unfavorable condition of the banking system has a major impact on the economy in Indonesia. The existence of monthly BSF (Banking Sector Fragility) index can be used to decide whether the national banking system is experiencing crisis at some point. This study aims to analyze how the effect of capital (CAR), profitability, liquidity, Gross Domestic Product (GDP), inflation and exchange rate against banking crisis based on Banking Sector Fragility Index listed in Indonesia Stock Exchange 2010-2014 period in Indonesia. Data analysis technique in this research is using statistical approach that is descriptive statistic analysis and logistic regression. The results showed that capital, Gross Domestic Product, inflation and exchange rate did not affect the banking crisis based on Banking Sector Fragility Index in Indonesia and profitability. Meanwhile liquidity had an effect on to banking crisis based on Banking Sector Fragility Index in Indonesia. Keywords: BSF Index, CAR, Profitability, Liquidity, GDP, Inflation, Exchange Rate